2020
DOI: 10.1111/ajad.12985
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Use and Sexual Risk Behaviors among Men Who Have Sex With Men in a Mexico‐US Border City

Abstract: Background and Objectives Methamphetamine (meth) use and its related risk behaviors for HIV among men who have sex with men (MSM) are a public health concern across the Mexico‐US border. This study aims to contribute to the limited literature of meth use and sexual risk behaviors among Latino MSM on the Mexico‐US border. Methods Data were drawn from the Meth Pilot Study (2014‐2015) among men who use meth (n = 100). Descriptive statistics and bivariate analysis comparing MSM to non‐MSM were conducted using Pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…Although they had similar rates to trans/women for crossing the border to El Paso in the past year, men had higher rates of crossing the border with meth and to obtain meth, overall. Previous analysis of this data among men found that ever obtained meth in El Paso was associated with having sex with men, 40 thus pointing to engagement in behaviors in El Paso that perhaps men in this study did not feel open to engage in Ciudad Juarez. Also, it was not assessed if taking meth to El Paso involved personal use or drug trafficking.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Although they had similar rates to trans/women for crossing the border to El Paso in the past year, men had higher rates of crossing the border with meth and to obtain meth, overall. Previous analysis of this data among men found that ever obtained meth in El Paso was associated with having sex with men, 40 thus pointing to engagement in behaviors in El Paso that perhaps men in this study did not feel open to engage in Ciudad Juarez. Also, it was not assessed if taking meth to El Paso involved personal use or drug trafficking.…”
Section: Discussionmentioning
confidence: 50%
“…The interview included quantitative and qualitative questions. All measures were collected using an adapted questionnaire comprised of several instruments previously developed and used in the region 40. Quantitative measures assessed in this study included measures for sociodemographic characteristics; cross-border mobility; lifetime drug and combination use; initiation into meth use; recent meth use (past 12 mo); and lifetime meth use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors’ knowledge, no studies have investigated the specific relationship between crystal meth use in the context of transactional sex and non-adherence to HIV treatment. However, studies among gbMSM in Canada and the US–Mexico border show that there may be a significant association between crystal meth use and transactional sex (Armstrong et al, 2021 ; Loza et al, 2020 ). Additionally, previous research among gbMSM in California found an association between transactional sex (in exchange for money, substances, or shelter) and higher HIV viral load levels (Javanbakht et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…B. Penisfraktur durch Ruptur des Corpus cavernosum, penetrierende Verletzungen durch Biss, stumpfe Hodenverletzungen) durch riskante sexuelle Praktiken unter Substanzeinfluss (u. a. bei sog. „Chemsex“ [ 67 69 ]). Das Drogenscreening untersucht, ob die vorliegende Symptomatik mit psychotropen Substanzen (z.…”
Section: Ergebnisse Und Diskussionunclassified